Fair Value: a Critical Analysis - Gutiérrez San Juán, Sergio Antonio
The aim of this paper is to monitor compliance with economic assumptions of transparency of information in the course of historical value accounting fair value accounting scenarios of imperfect markets, in order to validate the usefulness and relevance of the concept of fair value.